2012
DOI: 10.1007/s10753-012-9540-8
|View full text |Cite
|
Sign up to set email alerts
|

Stevioside Protects LPS-Induced Acute Lung Injury in Mice

Abstract: Stevioside, a diterpene glycoside component of Stevia rebaudiana, has been known to exhibit anti-inflammatory properties. To evaluate the effect and the possible mechanism of stevioside in lipopolysaccharide (LPS)-induced acute lung injury, male BALB/c mice were pretreated with stevioside or dexamethasone 1 h before intranasal instillation of LPS. Seven hours later, tumor necrosis factor-α, interleukin-1β, and interleukin-6 in bronchoalveolar lavage fluid (BALF) were measured by using enzyme-linked immunosorbe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
28
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 55 publications
(29 citation statements)
references
References 31 publications
1
28
0
Order By: Relevance
“…Upon stimulation by LPS, IκB-α is phosphorylated and degraded [34]. Afterward, the released NF-κB is translocated to the nucleus where it regulates the expression of immune and inflammatory response related genes, such as inducible nitric oxide synthase (iNOS), TNF-α and IL-1β [35]. iNOS produces large quantities of NO upon stimulation, such as by proinflammatory cytokines (e.g., TNF-α and IL-1β) [36].…”
Section: Discussionmentioning
confidence: 99%
“…Upon stimulation by LPS, IκB-α is phosphorylated and degraded [34]. Afterward, the released NF-κB is translocated to the nucleus where it regulates the expression of immune and inflammatory response related genes, such as inducible nitric oxide synthase (iNOS), TNF-α and IL-1β [35]. iNOS produces large quantities of NO upon stimulation, such as by proinflammatory cytokines (e.g., TNF-α and IL-1β) [36].…”
Section: Discussionmentioning
confidence: 99%
“…Edema is a representative characteristic of inflammation (Yingkun et al, 2013). Mogroside V has been reported to inhibit ear edema in murine model.…”
Section: Discussionmentioning
confidence: 99%
“…Mizushina et al (2005) showed that isosteviol, as product by acid hydrolysis of the steviol glycoside, strongly inhibits DNA polymerase and topoisomerase II, in this way delaying the growth of three types of cancer cells. Yingkun et al (2013) conducted experiments on male BALB/c mice, which were administered stevioside or dexamethasone 1 h before nasal instillation of lipopolysaccharide, causing acute lung injury. It was observed that stevioside limited the lipopolysaccharide-induced lung injury and inhibited the production of proinflammatory cytokines, expression of cyclooxygenase II, inducible NO synthase as well as phosphorylation of IjB alpha and NF-jB.…”
Section: Hypoglycemic Effectmentioning
confidence: 99%